Impact of differential and time-dependent autophagy activation on therapeutic efficacy in a model of Huntington disease. Issue 6 (3rd June 2021) - Brattås, Per Ludvik; Hersbach, Bob A.; Madsen, Sofia; Petri, Rebecca; Jakobsson, Johan; Pircs, Karolina
ABSTRACT: Activation of macroautophagy/autophagy, a key mechanism involved in the degradation and removal of aggregated proteins, can successfully reverse Huntington disease phenotypes in various model systems. How neuronal autophagy impairments need to be considered in Huntington disease progression to achieve a therapeutic effect is currently not known. In this study, we used a mouse model of HTT (huntingtin) protein aggregation to investigate how different methods and timing of autophagy activation influence the efficacy of autophagy-activating treatment in vivo . We found that overexpression of human TFEB, a master regulator of autophagy, did not decrease mutant HTT aggregation. On the other hand, Becn1 overexpression, an autophagic regulator that plays a key role in autophagosome formation, partially cleared mutant HTT aggregates and restored neuronal pathology, but only when administered early in the disease progression. When Becn1 was administered at a later stage, when prominent mutant HTT accumulation and autophagy impairments have occurred, Becn1 overexpression did not rescue the mutant HTT-associated phenotypes. Together, these results demonstrate that the targets used to activate autophagy, as well as the timing of autophagy activation, are crucial for achieving efficient therapeutic effects.Abbreviations : AAV: adeno-associated viral vectors; ACTB: actin beta; BECN1: beclin 1, autophagy related; DAPI: 4ʹ, 6-diamidino-2-phenylindole; GO: gene ontology; HD: Huntington disease; HTT: huntingtin; ICQ: Li's intensity correlation quotient; IHC: immunohistochemistry; LAMP1: lysosomal-associated membrane protein 1; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; mHTT: mutant huntingtin; PCA: principal component analysis; PPP1R1B/DARPP-32: protein phosphatase 1 regulatory inhibitor subunit 1B; SQSTM1: sequestosome 1; TFEB: transcription factor EB; WB: western blot; WT: wild-type.